THE ROLE OF WORKPLACE SPIRITUALITY ON EMPLOYEE PERFORMANCE THROUGH ORGANIZATIONAL COMMITMENT - Setiawan, Audita; Limakrisna, Nandan; Warsindah, Lucy (Multifinance, 2025)
This study aims to explore the influence of workplace spirituality on employee performance, considering the mediating role of organizational commitment. A quantitative approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze data collected from questionnaires distributed to auditors in public accounting firms in the West Java region. The findings indicate that workplace spirituality has a significant positive impact on employee performance, with organizational commitment serving as an effective mediator. The high t-statistic value suggests that employee who experience meaning and connection in their work demonstrate higher levels of commitment, ultimately leading to improved performance. These findings align with previous literature stating that workplace spirituality can enhance commitment and performance through increased intrinsic motivation. The practical implications of this study highlight the importance of organizations fostering a work environment that supports employees’ spiritual values to enhance commitment and performance.